(untitled) (Journal of Management and Social Sciences, 2018)
The paper contends that the abolition of slave trade Great Britain in 1807 was â€œa product of growing European industrial expansionismâ€. Indeed, the promotion of socalled â€˜legitimate tradeâ€™, whatever that meant, as well as the Annexation and Cession of Lagos can be explained only by economic determinism. The paper concludes that the Annexation and Cession of Lagos in 1861 was patently violative of customary rules and principles of international law. Keywords Legitimate trade, annexation and cession of Lagos, International law